Changes in perinatal health in two birth cohorts (1997/1998 and 2010) in São Luís, Maranhão State, Brazil - Antônio Augusto Moura da Silva (Cadernos de Saúde Pública, 2015)
The objective of this study was to analyze changes in perinatal health in two birth cohorts started in 1997/1998 and 2010, respectively, in São Luís, Maranhão State, Brazil. A total of 2,493 live born infants were included in 1997/1998 and 5,166 in 2010. Low birth weight (LBW) rate did not change (8.5% in 1997/1998 and 8.6% in 2010). Preterm birth (PTB) rate also remained stable (13.2% in 1997/1998 and 13% in 2010). Teenage deliveries and births to single mothers decreased. Maternal schooling and prenatal care coverage increased. Intrauterine growth restriction (IUGR) decreased from 13.3% to 10.6% (p < 0.001). The perinatal mortality rate decreased from 36.6 to 20.7 per 1,000 (p < 0.001) and the infant mortality rate (IMR) dropped from 28.5 to 12.8 per 1,000 (p < 0.001). The cesarean rate increased from 34.1% to 47.5% (p < 0.001). In conclusion, despite favorable changes in socio-demographic, behavioral, and health service factors and decreasing rates of IUGR and perinatal and infant mortality, LBW and PTB remained stable, while the cesarean rate increased.